Cardiac autonomic profile in different sports disciplines during all-day activity - Sztajzel, J.; Jung, M.; Sievert, K.; Bayes De Luna, A. (The Journal of Sports Medicine and Physical Fitness, 2008)
AIM: Physical training and sport activity have a beneficial effect on cardiac autonomic activity. However, the exact impact of different types of sports disciplines on cardiac autonomic function is still unclear. The aim of this study was to evaluate the cardiac autonomic profile in different sports discplines and to determine their impact on cardiac autonomic function by using heart rate variability (HRV), a noninvasive electrocardiographic (ECG) analysis of the sympatho-vagal balance.